1972
DOI: 10.1017/s0021859600069100
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid composition of barley grain protein during development and germination

Abstract: SUMMARYThe amino acid composition of barley grain was studied during the maturation of the grain and during germination of the mature grain. Samples of the variety Proctor, grown at two nitrogen levels in each of the years 1969 and 1970, were analysed together with one sample of Sultan grown in 1970. It was found that during maturation the proportions of glutamic acid and proline increased and that the levels of these amino acids were highest in those samples with the highest total protein content. During ripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Higher levels of glutamine and amino acids synthesized from it, including arginine and proline ( Forde and Lea, 2007 ), all of which were significantly enhanced in B2, support the synthesis of hordeins, which make up 30-50% of the barley proteins ( Howard et al., 1996 ). This also agrees with the finding that levels of glutamic acid and proline were associated with high protein contents in barley seeds ( Smith, 1972 ). Furthermore, accumulation of osmolytes and compatible solutes such as proline in response to various stress factors has been associated with antioxidative defence, signalling and chelation of metals ( Hayat et al., 2012 ) and in spring barley, a protective role for proline in response to water shortage during spike formation was suggested to support seed development ( Frimpong et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Higher levels of glutamine and amino acids synthesized from it, including arginine and proline ( Forde and Lea, 2007 ), all of which were significantly enhanced in B2, support the synthesis of hordeins, which make up 30-50% of the barley proteins ( Howard et al., 1996 ). This also agrees with the finding that levels of glutamic acid and proline were associated with high protein contents in barley seeds ( Smith, 1972 ). Furthermore, accumulation of osmolytes and compatible solutes such as proline in response to various stress factors has been associated with antioxidative defence, signalling and chelation of metals ( Hayat et al., 2012 ) and in spring barley, a protective role for proline in response to water shortage during spike formation was suggested to support seed development ( Frimpong et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Folkes and Yemm (1958) observed that lysine in germination barley increased an average of 65% over that in ungerminated grain during a 10-day germination period at 22.5 °C. Smith (1972) reported that germination increased lysine but decreased cystine in barley grain. Nielsen et al (1978) found that germination increased nutritional quality in terms of lysine content as effectively in wheat grain as in barley and corn grain.…”
Section: Resultsmentioning
confidence: 99%
“… a Jiang et al [ 20 ]; b Sekhar and Reddy [ 21 ]; c Sterna et al [ 22 ]; d Waggle et al [ 23 ]; e Smith [ 24 ]; f Millward [ 25 ]; WHO/FAO/UNU: World Health Organization/Food and Agriculture Organization/United Nations University); AA: amino acid; EAA: essential amino acid; and NEAA: non-essential amino acid. …”
Section: Role Of Vegetable Proteins In Agriculture and Foodmentioning
confidence: 99%